Digital leadership and employee engagement in hybrid work environments: The role of trust and communication - Nurhidayah, Rika; Muliansyah, Dadah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2024)
In response to the increasing shift toward hybrid work arrangements, this study investigates the role of digital leadership in shaping employee engagement, emphasizing the mediating effects of trust in leadership and digital communication. Drawing on the Job Demands–Resources (JD–R) model and Social Exchange Theory, this research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on survey data collected from 385 employees working under hybrid systems in diverse organizational settings. The findings reveal that digital leadership has a significant positive direct effect on employee engagement (β = 0.36, p < 0.001). Furthermore, trust in leadership and digital communication both serve as partial mediators in this relationship, indicating that relational and communicative mechanisms are crucial for sustaining engagement in digitally mediated environments. The structural model explained 51% of the variance in employee engagement, demonstrating strong explanatory power. These results extend current leadership theory by contextualizing digital leadership within hybrid work structures and emphasizing the need for trust-building and high-quality communication. The study contributes to the HRM literature by offering actionable insights for organizations seeking to optimize leadership strategies and communication infrastructures in evolving digital workplaces. Despite limitations related to cross-sectional data and sample generalizability, the research provides a foundation for future longitudinal and cross-cultural investigations into digital leadership dynamics.